Troubled blood - Galbraith, Robert (Galbraith, Robert. Cormoran Strike novel., 2020)
While visiting his family in Cornwall, Private Detective Cormoran Strike agrees to take on a cold case involving a woman who went missing in mysterious circumstances in 1974, and as Strike and his partner in the agency, Robin Ellacott, investigate the disappearance, they come up against a fiendishly complex case with leads that include tarot cards, a psychopathic serial killer, and witnesses who cannot all be trusted.